A Computational Model for Biomechanical Effects of Arterial Compliance Mismatch - Fan He; Lu Hua; Li-jian Gao (Applied Bionics and Biomechanics)
Background. Compliance mismatch is a negative factor and it needs to be considered in arterial bypass grafting. Objective. A computational model was employed to investigate the effects of arterial compliance mismatch on blood flow, wall stress, and deformation. Methods. The unsteady blood flow was assumed to be laminar, Newtonian, viscous, and incompressible. The vessel wall was assumed to be linear elastic, isotropic, and incompressible. The fluid-wall interaction scheme was constructed using the finite element method. Results. The results show that there are identical wall shear stress waveforms, wall stress, and strain waveforms at different locations. The comparison of the results demonstrates that wall shear stresses and wall strains are higher while wall stresses are lower at the more compliant section. The differences promote the probability of intimal thickening at some locations. Conclusions. The model is effective and gives satisfactory results. It could be extended to all kinds of arteries with complicated geometrical and material factors.